Larger vertebral endplate concavities cause higher failure load and work at failure under high-rate impact loading of rabbit spinal explants. (April 2018) - Dudli, S.; Enns-Bray, W.; Pauchard, Y.; Römmeler, A.; Fields, A.J.; Ferguson, S.J.; Helgason, B.
Abstract: Vertebral fractures are among the most common of all osteoporosis related fracture types and its risk assessment is largely based on bone quality measures. Morphometric parameters are not yet considered, although endplate thickness and concavity shape were found to be important in fracture prediction in low-rate tests. We hypothesized that, under high-rate impact loading, the shape and size of the central endplate concavity are of key importance for fracture prediction. Therefore, we tested rabbit spinal segment explants in vitro under high-rate impact loading. With a combination of microCT to describe endplate morphometry, high-speed video imaging, and impact force measurement, endplate morphometry was correlated to the mechanical response. We found that endplate concavity shape and volume were important in describing the mechanical response: larger concavities caused higher failure load. We suggest a model for the fracture mechanism under high-rate impact loading, considering the morphometry of the endplates: wider and more voluminous concavities are protective whereas steeper slopes of the concavity edges and increasing bone volume fraction of the central endplate moiety are disadvantageous. Therefore, the shape and size of endplate morphometry are important in vertebral fracture prediction and should be considered included in vertebral fracture risk assessment. Graphical abstract: fx1 Highlights: High sampling-rate measures are required to study high-rate impact fractures. High-rate fractures were studied with μCT, 250 kHz force measures, 24 kHz videotaping. Endplate morphology was correlated with impact measures. Larger endplate concavities are protective against high-rate impact fracture. Concavity shape should be considered in high-rate impact fracture prediction.